Informal learning within the mother daughter dyad: Effect on behavior and attitude - Deanne G Yates 2077423 (Adult Education Research Conference, 2018)
This roundtable will explore informal learning within the mother-daughter dyad and the role of informal learning on their perceptions of aging. The focus will be on how mothers and daughters understand the importance making meaning from an experience, memory, or conversation for learning to occur.
Keywords: Informal learning; Meaning-making